Control of Fe3+ coordination by excess Cl− in alcohol solutions. Issue 28 (17th June 2022) - Nomura, Yunika; Inoue, Dai; Moritomo, Yutaka
Abstract : Fe 3+ coordination in alcohol solution can be controlled by the Cl − concentration ([Cl − ]). The coordination state changes from FeL6 (L: solvent molecule) to FeCl4 type via FeCl n L6− n with increases in [Cl − ]. Abstract : We spectroscopically investigated coordination state of Fe 3+ in methanol (MeOH) and ethanol (EtOH) solutions against Cl − concentration ([Cl − ]). In both the system, we observed characteristic absorption bands due to the FeCl4 complex at high-[Cl − ] region. In the MeOH system, the proportion ( r ) of [FeCl4 ] − exhibits a stationary value of 0.2–0.3 in the intermediate region of 10 mM < [Cl − ] < 50 mM, which is interpretted in terms of [FeCl n L6− n ] 3− n ( n = 1 and 2). In the EtOH system, r steeply increases from 0.1 at [Cl − ] = 1.5 mM to 0.7 at [Cl − ] = 3.5 mM, indicating direct transformation from [FeL6 ] 3+ to [FeCl4 ] − . We further found that the coordination change significantly decreases the redox potential of Fe 2+ /Fe 3+ .